PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS PETA INTERAKTIF UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 2 PEKANBARU - Syahrani, Rama; Ahmal, Ahmal; Nurdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low interest of students in learning history subjects, which is only around 35%, the use of media that is not optimal, and the minimal use of maps as a representative form of place elements used in learning. This research aims to (1) develop interactive map-based history learning media; (2) determine the feasibility of interactive map-based history learning media; and (3) increase the interest of class XI students of SMA Negeri 2 Pekanbaru in learning by using interactive map-based history learning media. This research uses the Research and Development (R&D) research method with the ADDIE development model. Based on the research results, the results for material expert validation were 92%, media expert validation was 92.7%, while for student response assessment in small groups it was 88.4%, and large groups it was 87.2%. For students' learning interest, it is known that there has been an increase before and after using interactive map-based history learning media in small and large groups, namely: 1) Feelings of pleasure 55.3% to 88.6% and 57.6% to 84.8%, 2) Attention 60% to 91% and 59.1% to 87.8%, 3) Feelings of interest 67% to 90% and 62.4% to 87.5%, and 4) Student involvement 54.6% to 84.6% and 50.9% to 82.3%. Thus, it can be concluded that interactive map-based history learning media is very suitable for use in history learning and is able to increase students' learning interest.